The Influence of Municipal Treated Wastewater on Morpho-Physiological Characteristics of Eucalyptus Plants - Silva, Julliana Alves da [UNESP]; Zanette, Michele Moraes [UNESP]; Cechin, Inês [UNESP] (Springer, 2014)
The effects of municipal-treated wastewater on growth and gas exchange characteristics were studied in eucalyptus plants cultivated in a greenhouse under continuous sub irrigation with 70 % Long Ashton solution as a control, 100 % treated wastewater, and treated wastewater diluted 50 % with tap water. Irrigation with wastewater resulted in a reduction of total dry matter per plant and the shoot-to-root ratio and increased specific leaf mass, irrespective of the dilution. The gas exchange characteristics were adversely affected by the irrigation with wastewater, with photosynthetic rates been negatively affected. Total chlorophyll and carotenoids content were reduced in plants grown under treated wastewater. The results demonstrated that when the eucalyptus plants were grown under treated wastewater as the only source of mineral nutrients they were able to produce nearly 50 % of the dry matter produced by the plants grown under appropriate mineral nutrient supply, irrespective of the dilution. Therefore, the contribution of mineral nutrients and organic matter from the treated wastewater used as agricultural irrigation will be significant in lower the fertilizer rates without reducing dry matter production per plant.
Keywords: Eucalyptus urograndis; Wastewater reuse; Sub irrigation; Biomass production; Photosynthesis